Long-term outcomes from Healthy Eating and Exercise Lifestyle Program for overweight people with heart disease and diabetes. (February 2016) - Alharbi, Muaddi; Gallagher, Robyn; Kirkness, Ann; Sibbritt, David; Tofler, Geoffrey
Background: The benefits of exercise and weight reduction for overweight or obese people with coronary heart disease and/or diabetes mellitus are well recognised. The Healthy Eating and Exercise Lifestyle Program demonstrated these outcomes at 4 months, but longer-term outcomes are not yet reported. Aim: To determine whether positive weight, body mass index, waist and exercise duration outcomes were sustained in the long term (12 months) and to identify the independent predictors of these outcomes at 4 and 12 months. Methods: Longitudinal design, combining data of all Healthy Eating and Exercise Lifestyle Program participants (intervention and wait-list control, n = 134). Participants had a body mass index between 27 and 39 kg/m 2 and had completed cardiac rehabilitation and/or diabetes education programmes. Healthy Eating and Exercise Lifestyle Program intervention included an active phase of two 1-hour group-based supervised structured exercise sessions every week for 4 months and four 90-minute group information and support sessions. The maintenance phase included one 90-minute group-based booster information session and three 15-minute goal-focused telephone follow-up calls over 8 months. Results: Participants had statistically significant reductions from baseline in weight, body mass index and waist circumference and improvements in exercise duration and capacity at 4 and 12 months. Time, self-efficacy, depressive symptoms and male gender were independent predictors for body mass index, waist and/or exercise duration ( p < 0.05). Conclusion: The Healthy Eating and Exercise Lifestyle Program was an effective programme to achieve and sustain weight loss and increase exercise participation over 1 year.